The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12931-017-0565-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute cigarette smoke exposure activates apoptotic and inflammatory programs but a second stimulus is required to induce epithelial to mesenchymal transition in COPD epithelium

Abstract: BackgroundSmoking and aberrant epithelial responses are risk factors for lung cancer as well as chronic obstructive pulmonary disease and idiopathic pulmonary fibrosis. In these conditions, disease progression is associated with epithelial damage and fragility, airway remodelling and sub-epithelial fibrosis. The aim of this study was to assess the acute effects of cigarette smoke on epithelial cell phenotype and pro-fibrotic responses in vitro and in vivo.ResultsApoptosis was significantly greater in unstimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…6,7 Cell death induced by smoking may trigger a local or systemic inflammatory response that results in endothelial cell activation, the promotion of a prothrombotic stage and atherosclerotic plaque formation. 8,9 The extent of systemic inflammation can be assessed by the plasma Creactive protein (CRP) levels. 10 head and neck cancer patients, independently of tumournode-metastasis (TNM) staging.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Cell death induced by smoking may trigger a local or systemic inflammatory response that results in endothelial cell activation, the promotion of a prothrombotic stage and atherosclerotic plaque formation. 8,9 The extent of systemic inflammation can be assessed by the plasma Creactive protein (CRP) levels. 10 head and neck cancer patients, independently of tumournode-metastasis (TNM) staging.…”
Section: Introductionmentioning
confidence: 99%
“…1 Bronchial epithelial cells (BECs) are involved in the pathophysiology of COPD through the release of cytokines and chemokines in response to cigarette smoke. 2 COPD exacerbations are an acute worsening of symptoms, often caused by viral or bacterial infection and resulting in further amplification of airway inflammation. 3 Inhaled corticosteroids (ICS) are anti-inflammatory drugs that prevent exacerbations and improve quality of life in COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…EMT in COPD may be activated by interactions among epithelial cells and fibroblasts [227], reminiscent of non-cell autonomous regulation of EMT in lung cancer [228]. A recent report showed that the acute effects of cigarette smoke and associated infection, together play an important role in driving complete EMT; thus an extra insult, such as an infection can further exaggerate EMT [76] leading to chronically remodelled airways as observed in COPD [229].…”
Section: Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%